Morphometric Comparison and Prognostic Analysis of Permanent Maxillary Central Incisors with Eruption Disturbances—A Cross-Sectional Study - Yuri Jeong; Jonghyun Shin; Soyoung Park; Taesung Jeong; Eungyung Lee (Children, 2024)
Aims: The aim of this study was to retrospectively compare the morphometrics of permanent maxillary central incisors with and without eruption disturbances, while simultaneously evaluating prognosis based on different factors. Materials and Methods: Seventy patients with unilateral permanent maxillary central incisor eruption disturbances were included. Within a group of 70 subjects, measurements were taken for both normally erupted central incisors and central incisors with eruption disturbances to determine the length of the roots and the volume of the teeth. Various factors, such as angulation of impaction, and vertical height of impaction, were assessed to investigate their correlation with surgical intervention. Results: Both the root length and tooth volume were significantly smaller in the eruption disturbance incisors than in the normally erupted incisors (p ≤ 0.001). Moreover, there was a statistically significant increase in surgical intervention among cases with no clear physical barrier (primary retention) (p < 0.05) or when adjacent normally erupted central incisors exhibited more than 2/3 of root development (p < 0.05). Conclusions: The results of this study numerically demonstrated the delayed tooth development of the permanent maxillary central incisors with unilateral eruption disturbances compared to appropriately erupted incisors by measuring root length and tooth volume. The absence of obstacles and the degree of root development in adjacent erupted incisors might serve as factors for clinicians to determine the necessity and timing of surgical intervention.